Innovation Model of Digital Library Management to Enhance Literacy Culture in Senior High Schools - Noviyanti Noviyanti; Siraj Siraj; Cut Khairani (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study aims to analyze how digital library innovations cultivate a reading culture in senior high schools. The specific objectives are to examine the planning, implementation, evaluation, and management models applied in school-based digital library programs. Using a qualitative multi-case study approach, data were collected from principals, librarians, subject teachers, and students of SMA Negeri 3 Unggul Sigli and SMA Sukma Bangsa Pidie through observation, interviews, and document analysis. The findings reveal that the planning stage aligns literacy programs with the school’s vision, mission, and budget allocations to ensure targeted outcomes. During implementation, librarians provide optimal services such as online catalogues, e-books, and reading challenges—that encourage active student participation and increase reading frequency. Continuous evaluation is conducted through audits, user surveys, and feedback mechanisms, allowing weaknesses to be corrected promptly while best practices are disseminated. Finally, the management model follows a collaborative cycle that includes needs assessment, resource digitization, staff capacity building, and periodic updates to maintain the relevance of collections. By integrating these elements, the study concludes that systematic innovation in digital library management effectively strengthens a sustainable literacy culture among senior high school students